Jane Tolmach biography (1976)
This brief biographical statement outlines Jane McCormick Tolmach's background and qualifications during her Assembly campaign. It notes her service as an Oxnard City Councilwoman since 1970 and former mayor, along with earlier work on the City Planning Commission, regional transportation bodies (SCAT and VCAG), flood control, public health, education, and tax policy. The summary highlights her education at UCLA and Smith College, her family life in Oxnard, and her long involvement in Democratic Party leadership. It also states that her candidacy is supported by prominent Democrats including Governor Brown and Senator Cranston.